Pengembangan Media Pembelajaran Digital dalam Meningkatkan Kreativitas dan Inovasi Guru pada Materi Ekosistem di Sekolah Dasar - Ruhaya Ruhaya; Silvi Listia Dewi; Nadia Aldyza (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to develop digital learning media to enhance teachers’ creativity and innovation in teaching ecosystem content at the elementary school level. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The ADDIE model was selected because it is systematic, flexible, and oriented toward user needs analysis and continuous evaluation, thereby producing effective and applicable learning products. The study was conducted in Cluster IV of Nibong District, involving SDN 1 Nibong and SDN 3 Nibong. Data collection techniques included observation, questionnaires, and documentation. The research instruments comprised expert validation sheets, response questionnaires, and learning achievement tests to measure the validity, practicality, and effectiveness of the developed media. Data analysis was carried out using descriptive analysis and product feasibility analysis. The results indicate that the digital learning media on ecosystem topics were developed based on an analysis of IPAS learning needs in elementary schools and were designed to be visually appealing, contextual, and interactive in accordance with students’ characteristics. The developed media cover ecosystem concepts, biotic and abiotic components, relationships among living organisms, food chains and food webs, and ecosystem balance, and are complemented with animations, illustrations, practice questions, summaries, and learning evaluations. Expert validation results showed a feasibility percentage of 90% from content experts and 89.23% from media experts, both categorized as very feasible. Small-scale and large-scale trials yielded feasibility percentages of 91% and 89%, respectively. The digital learning media proved effective in increasing student engagement and in fostering teachers’ creativity and innovation in IPAS learning. Therefore, the developed digital learning media are deemed feasible, practical, and effective for use in elementary schools.